Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/02688697.2018.1478061
|View full text |Cite
|
Sign up to set email alerts
|

MRI-verified “asleep” deep brain stimulation in Malta through cross border collaboration: clinical outcome of the first five years

Abstract: An MRI-guided and MRI-verified approach to DBS was successfully implemented through cross border collaboration with achievement of expected clinical results. This healthcare collaboration developed out of necessity and opportunity, taking advantage of a UK-based neurosurgeon from Malta. The UK healthcare system benefits from numerous immigrants at Consultant level. Such a mutually beneficial arrangement could enable such individuals to offer their expertise to citizens in the UK as well as their country of ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In this study, a reduction in dyskinesia duration (p < 0.001), disability (p = 0.009) and off period duration, and improvement of sleep disorders were observed. Other authors also reported significant improvement in off-medication UPDRS, levodopa-equivalent daily dose (LEDD), and quality of life [29,35]. Harries et al reported a long-term clinical outcome of more than 5 years [49].…”
Section: Is Mer Mandatory For Stn Dbs Surgery?mentioning
confidence: 98%
See 3 more Smart Citations
“…In this study, a reduction in dyskinesia duration (p < 0.001), disability (p = 0.009) and off period duration, and improvement of sleep disorders were observed. Other authors also reported significant improvement in off-medication UPDRS, levodopa-equivalent daily dose (LEDD), and quality of life [29,35]. Harries et al reported a long-term clinical outcome of more than 5 years [49].…”
Section: Is Mer Mandatory For Stn Dbs Surgery?mentioning
confidence: 98%
“…Successful clinical results on the intraoperative imaging to verify the accuracy of STN lead position instead of electrophysiological structure mapping or stimulation tests during DBS surgery have been reported [23,29,31,37,[40][41][42][43][44]. In recent studies on the advancement of intraoperative imaging, no significant clinical results were found when compared to awake DBS [16,30,37,45,46].…”
Section: Using Intraoperative Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with improvements and advances in magnetic resonance imaging (MRI), direct anatomic targeting of structures such as subthalamic nucleus (STN), globus pallidus interna (GPi), or even ventralis intermedius nucleus (VIM) is now possible. Next, in place of intraoperative electrophysiologic mapping of the structure or test stimulation of symptoms and side effects in the awake patient, the use of intraoperative imaging to verify lead accuracy has been reported in several studies of PD patients undergoing DBS under general anesthesia (“asleep” DBS) . The results demonstrated that the clinical outcomes, complication rates and costs were comparable to those in historical studies using MER to guide lead placement under local anesthesia .…”
Section: Introductionmentioning
confidence: 99%